2000
DOI: 10.1038/sj.mp.4000638
|View full text |Cite|
|
Sign up to set email alerts
|

Family-based linkage disequilibrium mapping using SNP marker haplotypes: application to a potential locus for schizophrenia at chromosome 22q11

Abstract: Family-based linkage disequilibrium mapping using SNP markers is expected to be a major route to the identification of susceptibility alleles for complex diseases. However there are a number of methodological issues yet to be resolved, including the handling of extended haplotype data and analysis of haplotype transmission in sib-pair or family trio samples. In the present study, we have analysed two dinucleotide repeat and six SNP markers at the COMT locus at chromosome 22q11, a region implicated in psychosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
97
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 42 publications
5
97
1
1
Order By: Relevance
“…For the present analysis minimum haplotype frequencies were set at 0.03 and ambiguity set at 3, ie haplotypes which occurred with a frequency of less than 3% were excluded and if there are more than three possible parental haplotypes the family was excluded. 10 …”
Section: Discussionmentioning
confidence: 99%
“…For the present analysis minimum haplotype frequencies were set at 0.03 and ambiguity set at 3, ie haplotypes which occurred with a frequency of less than 3% were excluded and if there are more than three possible parental haplotypes the family was excluded. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this notion, several [although not all (Semwal et al, 2001)] studies using the family-based transmission disequilibrium test have shown the high-activity Val allele of COMT, which presumably increases dopamine catabolism, to be preferentially transmitted to schizophrenic offspring Kunugi et al, 1997;Li et al, 2000Li et al, , 1996. Interestingly, this Val 108/158 Met functional polymorphism has been reported to be associated with schizotypal personality traits even in healthy individuals, and in the same direction as observed in schizophrenic patients, that is, increased Val allele frequency (Avramopoulos et al, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…5,6 More importantly, genetic associations to genes in these linkage regions have been confirmed recently in multiple samples. [7][8][9] These genes include, among others, DISC1 on 1q, [10][11][12] DTNBP1 (dysbindin) on 6p, 13,14 NRG1 on 8p, 15 catechol-O-methyltransferase (COMT) on 22q, 16,17 DAOA (G72) on 13q 18,19 and RGS4 on 1q. [20][21][22] The linkage findings represented an important step, enabling targeted searches within defined regions of the genome.…”
Section: Introductionmentioning
confidence: 99%